High-Resolution Two-Locus Clonal Typing of Extraintestinal Pathogenic Escherichia coli - Weissman, Scott J. (American Society for Microbiology, 2012)
Multilocus sequence typing (MLST) is usually based on the sequencing of 5 to 8 housekeeping loci in the bacterial chromosome and has provided detailed descriptions of the population structure of bacterial species important to human health. However, even strains with identical MLST profiles (known as sequence types or STs) may possess distinct genotypes, which enable different eco- or pathotypic lifestyles. Here we describe a two-locus, sequence-based typing scheme for Escherichia coli that utilizes a 489-nucleotide (nt) internal fragment of fimH (encoding the type 1 fimbrial adhesin) and the 469-nt internal fumC fragment used in standard MLST. Based on sequence typing of 191 model commensal and pathogenic isolates plus 853 freshly isolated clinical E. coli strains, this 2-locus approach—which we call CH (fumC/fimH) typing—consistently yielded more haplotypes than standard 7-locus MLST, splitting large STs into multiple clonal subgroups and often distinguishing different within-ST eco- and pathotypes. Furthermore, specific CH profiles corresponded to specific STs, or ST complexes, with 95% accuracy, allowing excellent prediction of MLST-based profiles. Thus, 2-locus CH typing provides a genotyping tool for molecular epidemiology analysis that is more economical than standard 7-locus MLST but has superior clonal discrimination power and, at the same time, corresponds closely to MLST-based clonal groupings.